Protocol at the Crossroads: Rethinking anti-trafficking law from an Indian labour law perspective - Kotiswaran, Prabha (Anti-Trafficking Review, 2015)
As we approach the fifteenth anniversary of the United Nations Trafficking Protocol, we can discern several phases of its diffusion, materialisation and interpretation in domestic criminal law regimes across the world. Although not exclusively preoccupied with sex work and sex trafficking anymore, the fact remains that the inordinate attention on trafficking in Western industrialised economies is disproportionate to the extent of the problem. Only 7% of the world’s 20.9 million forced labourers are in developed economies while 56% are in Asia Pacific. Yet in BRIC countries like India, with a substantial majority of the world’s trafficked victims and where 90% of all trafficking is domestic, trafficking has gained policy resonance only relatively recently. Even as India remains an active site for sexual humanitarianism with international and local abolitionist groups actively targeting sex workers, the article argues that less developed countries like India can play a crucial role in reorienting international anti-trafficking law and policy. Towards that goal, this article offers India’s bonded, contract and migrant labour laws as a robust labour law model against trafficking in contrast to the criminal justice model propagated by the Trafficking Protocol worldwide.